Identifikasi Fungsi Dominan dan Efektivitas Taman Kota di Kota Jayapura: Studi Kasus Taman Imbi dan Taman Mesran - Farhan Alfikri Pelu; Irja Tobawan Simbiak; Sudiro Sudiro (Fakultas Teknik Universitas Cenderawasih, 2026)
This study examines the effectiveness of urban city parks as a form of Urban Green Open Space (UGOS) in Jayapura City, focusing on Imbi Park (2,347.20 m²) and Mesran Park (2,122.88 m²). A mixed-methods approach combined direct observation of six park characteristics with a questionnaire-based rating-scale assessment of nineteen functional variables covering socio-cultural, aesthetic, and economic functions. Data were collected from 100 visitors and 31 street vendors, and analyzed using descriptive statistics and scoring analysis in accordance with Minister of Public Works Regulation No. 05/PRT/M/2008. Both parks share three dominant functions socio-cultural, aesthetic, and economic while the ecological function is present but not dominant. For Imbi Park, the socio-cultural function was moderately effective (1.8–2.0), aesthetic moderately effective to effective (2.4–2.6), and economic moderately effective (1.8–1.9). For Mesran Park, socio-cultural and aesthetic functions were moderately effective (1.8–2.2), while the economic function was ineffective (1.6). The main weaknesses across both parks are the unavailability of security posts and limited diversity of park-produce-based economic activities. The study recommends developing supporting facilities and a park-profile web portal to improve effectiveness and information accessibility.